Climate Risk Management in Agricultural Extension – Zambia Reference Guide - Dinku, Tufa; Hansen, James; Trzaska, Sylwia; Amanda, Grosi; Huyer, Sophia; Moore, Maya; Sakumona, Mushekwa; Sakala, Isabel; Lungu, Olipa; Mangaba, Darlington (2024)
Improvements in the weather and climate information available in Ghana provide new opportunities for agricultural extension personnel to help farmers better manage the risks that they face, and to adapt recommended technology packages to local climatic conditions. This reference guide provides the reference materials for the 2-week Climate Risk Management in Agricultural Extension course that aims to equip agricultural extension workers in Zambia to access, understand and incorporate climate information into their professional work. It is designed to provide foundational knowledge on climate and agricultural decision making; and practical tools to analyze climate-related risks, use appropriate weather and climate information to support agricultural decisions, communicate complex climate information effectively with farmers, and integrate climate services into agricultural extension activities.